2020
DOI: 10.1371/journal.pone.0231382
|View full text |Cite|
|
Sign up to set email alerts
|

Cross-cultural adaptation and psychometric testing of the Arabic version of the Modified Low Back Pain Disability Questionnaire

Abstract: BackgroundThe Modified Oswestry Low Back Pain Disability Questionnaire (MODQ) is used for evaluating the functional disability in patients with low back pain (LBP). However, the measurement characteristics of the MODQ among Arab patients are unknown. In this study, we aimed to translate and cross-culturally adapt the MODQ into Arabic and evaluate its psychometric properties. MethodsAn Arabic version of the MODQ was developed through forward translation, translation synthesis, and backward translation. Sixty-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 74 publications
4
15
0
1
Order By: Relevance
“…(1,14,17,35,42). In present study, mean age of patients was 39.7 years, that is quite similar (36-40 years) to the previous research studies (1,14,32,55) but in contrast few studies have enrolled patients with slightly higher mean age (40-52 years) (17,35,42,52) In the present study, internal consistency was found to be excellent with 0.89 Cronbach's alpha value, which is also in the range of results of previous studies (0.75-0.99) (3,36,47,(56)(57)(58)(59)(60)(61) The item total correlation between single item and total score of ODI-U ranged between 0.51-0.76 which is quite similar to the ndings of German version of ODI (0.58-0.72). (62) However, in the study of Liu et al (Chinese ODI version) the item total correlation was reported as slightly high (0.59-0.83).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…(1,14,17,35,42). In present study, mean age of patients was 39.7 years, that is quite similar (36-40 years) to the previous research studies (1,14,32,55) but in contrast few studies have enrolled patients with slightly higher mean age (40-52 years) (17,35,42,52) In the present study, internal consistency was found to be excellent with 0.89 Cronbach's alpha value, which is also in the range of results of previous studies (0.75-0.99) (3,36,47,(56)(57)(58)(59)(60)(61) The item total correlation between single item and total score of ODI-U ranged between 0.51-0.76 which is quite similar to the ndings of German version of ODI (0.58-0.72). (62) However, in the study of Liu et al (Chinese ODI version) the item total correlation was reported as slightly high (0.59-0.83).…”
Section: Discussionsupporting
confidence: 88%
“…The current study has recruited more males 61 (56.45%) than females 47 (44%) which is comparable to the previous studies (54-80%) (32,52,55). However many studies have recruited more females (52-66%) than males.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations